Fight against Obesity Mobile Application - Qin, Ching Zhen; Muhamad Adnan, Muhamad Hariz (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
The focus of this research was basic workout guide which provide steps for workout, suggested healthy nutrition and information about health disease. The target user of this research was the adult who confront with overweight and obesity problem. Workout is a set of energetic action or exercise that people can do it everywhere. This research aimed to help the target user to practice the healthy lifestyle by starting workout and eating with balance nutrition. The software of this research will be performed in mobile application. A quantitative method is used to collect the data on user acceptance on the developed mobile application. There were 30 respondents from UPSI invited to answer the questionnaire after using the Fight against Obesity mobile application. The result showed overall mean equal to 4.07, which mean the majority respondents were accept Fight against Obesity Mobile Application. For adult who owned a mobile phone, they can just download this mobile application and start to train themselves to be discipline and solving their weight problem.